Food production and climate protection-What abandoned lands can do to preserve natural forests - Knoke, T. (2013)
Approaches to reconciling food production with climatic and environmental protection often require agricultural intensification. The production of more food per unit of agricultural land through sustainable intensification is intended to enable the protection of natural ecosystems elsewhere (land sparing). However, there are problems associated with agricultural intensification; such as soil erosion, eutrophication or pollution of water bodies with chemicals, landscape homogenization and loss of biodiversity; for which solutions have not yet been found. Reuse of abandoned agricultural lands which are abundant throughout the world to address the rising demand for food is a potentially important alternative, which up to now has been widely ignored. To test the power of this alternative, equilibrium economic land allocation to various land-use practices by risk-avoiding tropical farmers in Ecuador was simulated. The reestablishment of pastures on abandoned cattle lands lowered prices for pasture products, and also triggered conversion of existing pasture into cropland. The resulting land-use change increased total annual food production in a moderate scenario from the current level of 17.823.1 petacalories (1015 calories), which amounted to a production increase of 30%. At the same time, there was a 19% reduction in the amount of payments to farmers required to preserve tropical forests one of the world s greatest terrestrial carbon stores.